2010
DOI: 10.2175/106143010x12609736967288
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Focused‐Pulsed Treated Waste Activated Sludge as a Supplemental Electron Donor for Denitrification

Abstract: We evaluated the feasibility of using waste activated sludge (WAS) from a wastewater treatment plant as an internal electron donor to fuel denitrification, by increasing its bioavailability with Focused-Pulsed (FP) technology. The focused-pulsed treatment of WAS (producing FP-WAS) increased the semi-soluble chemical oxygen demand (SSCOD) by 26 times compared with the control WAS. The maximum denitrification rate of FP-WAS (0.25 g nitrate-nitrogen [NO 3 2 -N]/g volatile suspended solids [VSS]?d) was greater tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Numerous sludge treatment technologies to increase VFAs have been developed, mainly including physical processes (such as mechanical treatment, focused-pulsed, and ultrasound) [59][60][61], fermentation processes (alkaline and acid fermentation) [61][62][63][64][65], and their combination [66,67]. These techniques are used to break sludge floc into a small fraction of soluble COD (SCOD, such as VFAs) [59], or translate long and non-degradable organic substances into short and biodegradable COD [68].…”
Section: Techniques Applied For Vfas Production From Sludgementioning
confidence: 99%
See 1 more Smart Citation
“…Numerous sludge treatment technologies to increase VFAs have been developed, mainly including physical processes (such as mechanical treatment, focused-pulsed, and ultrasound) [59][60][61], fermentation processes (alkaline and acid fermentation) [61][62][63][64][65], and their combination [66,67]. These techniques are used to break sludge floc into a small fraction of soluble COD (SCOD, such as VFAs) [59], or translate long and non-degradable organic substances into short and biodegradable COD [68].…”
Section: Techniques Applied For Vfas Production From Sludgementioning
confidence: 99%
“…The result showed that denitrification rates improved after the addition of disintegrated sludge (36.7 mg NO 3 -N g −1 /VSS h −1 ) compared with the control (30.2 mg NO 3 -N g −1 /VSS h −1 ) and were even higher than acetate as an additional source (34.7 mg NO 3 -N g −1 /VSS h −1 ). Lee et al [61] evaluated the feasibility of focused-pulsed, and the result showed that VFAs increased 5.1-fold relative to untreated WAS. The batch-test denitrification rate of focused-pulsed-WAS (0.25 gNO 3 -N/g VSS d) was higher than that of untreated WAS (0.05 g NO 3 -N/g VSS d) and methanol (0.15 gNO 3 -N/g VSS d).…”
Section: Techniques Applied For Vfas Production From Waste Activated Sludgementioning
confidence: 99%
“…Microbiological analysis of sludge revealed significant increases of organics in the presence of several methanogenic microbiological species. Bench-scale of FP pretreatment applied to secondary sludge had showed rapid denitrification kinetics because of the electron donor having high SCOD and ammonia concentrations (Lee et al 2010). At a treatment intensity of 16 kWh/m 3 the semisoluble chemical oxygen demand (COD) had increased by 16 times.…”
Section: Sludges and Wastesmentioning
confidence: 99%
“…The pre-treatment process breaks down floc to increase the availability of intracellular organic material that is solubilized in the liquid. Different pre-treatment methods can be used including chemical [4], biological [5][6][7], mechanical [8,9], thermal [4,8,[10][11][12][13] and non-thermal pulse powered processes [14][15][16]. Of these methods, thermal pre-treatment processes have been shown to be highly effective, and the design of efficient heating methods to pre-treatment wastewater sludge has motivated this research work.…”
Section: Introductionmentioning
confidence: 99%